INTEGRATION OF ISLAMIC VALUES WITH A MULTIDISCIPLINARY APPROACH IN ISLAMIC RELIGIOUS EDUCATION LEARNING - Tondi Martua Nasution; Elfi Idayani Daulay; Nila Wahyuni Nasution; Nur Laila Annisa Lubis; Mohd Rafiq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study explores the integration of Islamic values with a multidisciplinary approach in Islamic Religious Education (Pendidikan Agama Islam/PAI) learning. The objective of this research is to examine how Islamic values can be effectively incorporated into various scientific perspectives to enhance students’ understanding, critical thinking, and holistic character development. The study employs a qualitative descriptive method through literature review and conceptual analysis of relevant educational theories and previous studies. The findings indicate that integrating Islamic values with disciplines such as sociology, psychology, linguistics, and science education can enrich learning experiences and make Islamic education more contextual, meaningful, and applicable to real-life situations. This integrative approach also strengthens students’ spiritual, moral, and intellectual competencies simultaneously. Furthermore, the study concludes that multidisciplinary integration in PAI not only supports cognitive achievement but also fosters character building aligned with Islamic teachings. The implication of this study suggests that educators should adopt flexible and collaborative teaching strategies to bridge religious knowledge with contemporary academic disciplines. However, the study is limited to theoretical analysis and does not include empirical classroom implementation, which opens opportunities for further research in experimental settings. The originality of this study lies in its emphasis on a structured integration model of Islamic values across multiple disciplines within PAI learning contexts.